Pseudo-differential operators analysis, applications and computations - Rodino, L. (Luigi); Wong, M. W. 1951- (Man Wah); Zhu, Hongmei (Operator theory, advances and applications, 2011)
This volume consists of eighteen peer-reviewed papers related to lectures on pseudo-differential operators presented at the meeting of the ISAAC Group in Pseudo-Differential Operators (IGPDO) held at Imperial College London on July 13?18, 2009. Featured in this volume are the analysis, applications and computations of pseudo-differential operators in mathematics, physics and signal analysis. This volume is a useful complement to the volumes ?Advances in Pseudo-Differential Operators?, ?Pseudo-Differential Operators and Related Topics?, ?Modern Trends in Pseudo-Differential Operators?, ?New Developments in Pseudo-Differential Operators? and ?Pseudo-Differential Operators: Complex Analysis and Partial Differential Equations? published in the same series in, respectively, 2004, 2006, 2007, 2009 and 2010.